Alterations in Kernel Proteome after Infection with Fusarium culmorum in Two Triticale Cultivars with Contrasting Resistance to Fusarium Head Blight - Perlikowski, Dawid; Wiśniewska, Halina; Kaczmarek, Joanna; Góral, Tomasz; Ochodzki, Piotr; Kwiatek, Michał; Majka, Maciej; Augustyniak, Adam; Kosmala, Arkadiusz (Frontiers in Plant Science, 2016)
Triticale was used here as a model to recognize new components of molecular mechanism of resistance to Fusarium head blight (FHB) in cereals. Fusarium-damaged kernels of two lines distinct in levels of resistance to FHB were applied into a proteome profiling using two-dimensional gel electrophoresis (2-DE) to create protein maps and mass spectrometry to identify the proteins differentially accumulated between the analyzed lines. This proteomic research was supported by a measurement of alpha- and beta-amylase activities, mycotoxin content and fungal biomass in the analyzed kernels. The 2-DE analysis indicated a total of 23 spots with clear differences in a protein content between the more resistant and more susceptible triticale lines after infection with F. culmorum. A majority of the proteins were involved in a cell carbohydrate metabolism, stressing the importance of this protein group in a plant response to Fusarium infection. The increased accumulation levels of different isoforms of plant beta-amylase were observed for a more susceptible triticale line after inoculation but these were not supported by a total level of beta-amylase activity, showing the highest value in the control conditions. The more resistant line was characterized by a higher abundance of alpha-amylase inhibitor CM2 subunit and simultaneously a lower activity of alpha-amylase after inoculation. We suggest that the level of pathogen alpha-amylase and plant beta-amylase activities could be components of plant-pathogen interaction associated with the resistance of triticale to Fusarium head blight.